Bulgaria in Passing: The Images of Old and New Bulgaria in Travelogues by Patrick Leigh Fermor and Nick Hunt - Boycheva, Maya (Research Papers, 2020)
The article compares intertextually two travelogues about Bulgaria, as seen by British travel writers in two different historical periods. The continuity of the representative matrix is foregrounded by identifying recurrent tropes and motives along with the stable binaries of Self/Other and East/West. The article posits that the travelogues in question are political texts reifying the established paradigm of controlled representation of Bulgaria which problematizes all things Bulgarian as alien, eastern or peripheral. The article also highlights the emergence of new representative strategies which hint at the vulnerability of the dominant negative discourse.